Analysis of the Quality of Public Services in the Health Sector at Centro Da Saude Vera-Cruz, Municipiu Dili, East Timor - Inácio Sarmento Viegas; Desideius Priyo Sudibyo; Rino Ardhian Nugroho (Green Publisher, 2024)
This study aims to assess user satisfaction and identify areas for improvement in the quality of health services at Centro da Saude Vera-Cruz, Municipio Dili, Timor-Leste. Specifically, it evaluates key service dimensions including tangibility, reliability, responsiveness, assurance, and empathy from the perspective of service users. A quantitative approach was employed, utilizing a Likert scale to measure respondents' perceptions across these dimensions. The data were analyzed using frequency distribution and cross-tabulation based on respondent characteristics such as age and marital status. The results indicate that most respondents expressed agreement, strong agreement, and high satisfaction with the health services provided, although a minority expressed dissatisfaction. Further analysis showed that respondents aged 31-40 were more likely to express strong agreement with service quality. Overall, among the 60 respondents surveyed, the findings reflect a generally positive perception of the health services at Centro da Saude Vera-Cruz, while highlighting certain aspects where dissatisfaction remains. These insights offer a foundation for targeted improvements in service delivery.